Relapsing neuromyelitis optica: long term history and clinical predictors of death. Issue 10 (17th September 2009) - Cabre, P; González-Quevedo, A; Bonnan, M; Saiz, A; Olindo, S; Graus, F; Smadja, D; Merle, H; Thomas, L; Cabrera-Gomez, J A
Abstract : Background: Relapsing neuromyelitis optica (RNMO) is an uncommon but devastating inflammatory disorder of the central nervous system. Long term history in a wide series of RNMO is required for better knowledge of the course of the disease and identification of patients at high risk of death. Methods: Clinical features of patients with RNMO (88 women/eight men) obtained from the geographic Caribbean database (Cuba and French West Indies) were used to determine the progression of disability and to identify clinical predictors of death. Results: Median age at onset of RNMO was 29.5 years (range 11–74). Median duration of disease was 9.5 years (1–40). Median relapse rate was 0.7 attack/patient/year (0.1–3). 66 patients experienced severe visual loss in at least one eye and 46 in both eyes. Median time from onset to unilateral and bilateral severe visual loss was 3 and 15 years, respectively. Median times to reach Kurtzke Disability Status Scale 3, 6 and 8 from onset of RNMO were 1, 8 and 22 years. There were 24 deaths (25%); within 5 years in 63% of cases. A higher attack frequency during the first year of disease (p = 0.009), blindness (p = 0.04) and sphincter signs at onset (p = 0.02) and lack of recovery of first attack (p = 0.003) were independently associated with a shorter time to death. Conclusion: RNMO is a very rapidly disabling disease affecting primarily young women. This study has identified clinical features that predict a poor outcome. These findings suggest that early and aggressive immunotherapy might be warranted in RNMO.